Visible-light-responsive ternary Z-type semiconductor composite material and preparation method and application thereof
By preparing Al2O3/Cr2O3@C3N4 heterojunction materials, the problem of poor ibuprofen degradation effect of semiconductor materials under visible light in the prior art has been solved, realizing efficient and stable ibuprofen degradation, reducing production costs and environmental pollution.
Patent Information
- Application Number
- CN202511126544.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-12
- Publication Date
- 2025-11-25
AI Technical Summary
Existing semiconductor materials are not effective at degrading ibuprofen under visible light. Traditional semiconductor materials have limited photoreactivity in the ultraviolet region and consume a lot of energy. Furthermore, the preparation of g-C3N4 heterojunction with metal oxide is complex and costly, making it difficult to effectively remove ibuprofen from water.
A visible light-responsive ternary Z-type semiconductor composite material, Al2O3/Cr2O3@C3N4, was prepared by nesting Al2O3 and Cr2O3 with protonated C3N4 to form a heterojunction, thereby optimizing the electron transfer path and carrier separation efficiency of the material and improving its catalytic activity and stability.
The method achieves efficient degradation of ibuprofen in a weakly alkaline environment with a degradation rate of 97.58%. The material can drive the reaction under visible light, which reduces production costs. Furthermore, the degradation products are short-chain carboxylic acids that can participate in the natural carbon cycle, solving the problems of high energy consumption and complexity of traditional methods.
Smart Images

Figure CN121003987A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a visible light responsive ternary Z-type semiconductor composite material and its preparation method and application, belonging to the technical field of environmental catalytic materials. BACKGROUND
[0002] Ibuprofen (IBU) as a commonly used non-steroidal anti-inflammatory drug (NSAID), due to the fact that ibuprofen is insoluble in neutral and weakly acidic aqueous solutions, its concentration in nature is usually very low, between approximately 200 ng / L and 370 µg / L. This poses a challenge for the removal of ibuprofen by biodegradation methods, especially in alkaline environments. Long-term exposure to environments containing ibuprofen not only interferes with the normal development of aquatic organisms' zygotes and fetuses, but also has adverse effects on the development of human ovaries and zygotes. For this reason, relevant research is dedicated to the development of oxidative catalysts for the removal of ibuprofen from water. However, traditional semiconductors, due to their large band gap, have limited photo-reactivity only in the ultraviolet region, which not only consumes a lot of energy, but also produces complex byproducts, making the study of degradation pathways complex. In contrast, visible light provides a cleaner alternative, avoiding the above-mentioned shortcomings.
[0003] Graphitic carbon nitride (g-C3N4) has high activity under visible light and stable chemical properties, but the carrier separation efficiency is low. The application of g-C3N4 / metal heterostructure is limited due to the complexity of the mixed metal semiconductor catalyst process and the high cost of some metals. The degradation effect of ibuprofen is significantly enhanced by combining g-C3N4 with other semiconductor materials, which still has a lot of room for improvement. Currently, there have been reports on the study of g-C3N4 / metal oxide heterojunctions, but the study of g-C3N4 nested with Al2O3 and Cr2O3 to form a heterojunction is still rare. This structure has the advantages of Al2O3 and Cr2O3 as a heterojunction material, and is expected to improve the stability and interface bonding force of the heterojunction under visible light, thereby achieving efficient and stable degradation of ibuprofen. However, it is difficult to combine the hydrophobicity of g-C3N4 with the hydrophilicity of Al2O3, and Cr2O3 is prone to photo-corrosion under light, which not only reduces the catalytic activity, but also may cause secondary environmental pollution, making the preparation of this heterojunction extremely challenging. In view of the above problems, the present application prepares a visible light responsive ternary Z-type semiconductor composite material through the synergistic effect of the preparation process and raw materials, and the preparation mechanism is as shown in Figure 1 (a), which can efficiently and stably degrade ibuprofen, providing a feasible solution to the bottleneck of the prior art. SUMMARY
[0004] One of the purposes of the present application is to provide a visible light response ternary Z-type semiconductor composite material Al2O3 / Cr2O3@C3N4 (ACC), which is a heterojunction formed by nesting Al2O3 / Cr2O3 composite and protonated C3N4 at a mass percentage of 5-50%.
[0005] Preferably, the Al2O3 is in gamma crystal form; the Cr2O3 is in hexagonal crystal form; and the protonated C3N4 is layered porous graphite phase carbon nitride loaded with amorphous alumina coated hexagonal chromium oxide.
[0006] The second purpose of the present application is to provide a preparation method of a visible light response ternary Z-type semiconductor composite material, which specifically comprises the following steps: (1) potassium dichromate is prepared into an aqueous solution, concentrated sulfuric acid is added to the potassium dichromate aqueous solution for reaction, an organic solvent and a base are added to the solution after reaction for adjusting the pH value of the solution.
[0007] (2) the solution after adjusting the pH value is heated, then aluminum chloride and ammonia are added to the solution for reaction, the solid product after the reaction is filtered, dried (preferably oven drying), then calcined (preferably calcination in a muffle furnace), and the solid product after calcination is ground to obtain Al2O3 / Cr2O3 composite powder.
[0008] (3) urea is calcined (preferably in a tube furnace) to obtain a solid sample, and the solid sample is washed with acid and dried to obtain porous g-C3N4 powder.
[0009] (4) Al2O3 / Cr2O3 composite powder and porous graphite phase carbon nitride powder are weighed according to the proportion and mixed to form a mixed powder, then the mixed powder is suspended with water, followed by ultrasonic and stirring, then centrifugal drying (preferably in a vacuum drying oven) to obtain Al2O3 / Cr2O3@C3N4 (ACC).
[0010] Preferably, the concentration of the potassium dichromate aqueous solution in step (1) is 80 g / L.
[0011] Preferably, in step (1), the concentrated sulfuric acid is added to the potassium dichromate aqueous solution at a mass-volume ratio of 2 g:3 mL of potassium dichromate to concentrated sulfuric acid.
[0012] Preferably, in step (1), the concentrated sulfuric acid is added to the potassium dichromate aqueous solution for reaction for 30 min; the organic solvent is anhydrous ethanol, which is added to the solution after reaction at a volume ratio of 10:3 of the organic solvent to concentrated sulfuric acid; and the base is sodium hydroxide.
[0013] Preferably, the pH of the solution after the reaction in step (1) is adjusted to neutral.
[0014] Preferably, the solution after pH adjustment in step (2) is heated to 70 DEG C.
[0015] Preferably, the aluminum chloride and ammonia are added to the solution after pH adjustment in step (2) in a mass-volume ratio of 1.35 g:5 mL:30 mL.
[0016] Preferably, the mass percentage concentration of the ammonia in step (2) is 25%.
[0017] Preferably, the reaction time of the aluminum chloride, ammonia and the solution after pH adjustment in step (2) is 2-3 h; the drying condition of the solid product is drying at 105 DEG C overnight; and the calcination condition of the solid product is calcination at 380-430 DEG C for 4-5 h.
[0018] Preferably, the calcination condition in step (3) is calcination at 520-580 DEG C for 2-3 h under a nitrogen atmosphere.
[0019] Preferably, the acid washing process in step (3) is stirring and acid washing the solid sample with 6 mol / L hydrochloric acid solution for 4 h.
[0020] Preferably, the stirring time of the mixed powder in the suspension treatment in step (4) is 4 h.
[0021] Preferably, the drying condition of the mixed powder in step (4) is drying at 60 DEG C overnight.
[0022] The third object of the present application is to provide an application of the visible light responsive ternary Z-type semiconductor composite material in catalytic degradation of ibuprofen in water.
[0023] The mechanism of the present application is as follows: The preparation process of the present application makes C3N4, Al2O3 and Cr2O3 exhibit a significant synergistic effect under visible light irradiation: the photo-generated electrons generated by C3N4 under light excitation form a high-efficiency bidirectional electron transfer channel between the Al2O3 / Cr2O3 heterostructure, and this electron transfer mechanism effectively promotes the separation of photo-generated carriers in C3N4. The synergistic effect of the preparation process and raw materials of the present application significantly improves the adsorption and activation capacity of the material surface oxygen vacancy to oxygen, promotes the generation of superoxide radicals, and thus realizes the efficient oxidative degradation of ibuprofen.
[0024] The beneficial effects of the present application are as follows: (1) Since ibuprofen is insoluble in neutral and weakly acidic aqueous solutions, its natural concentration is usually between 200 ng / L and 370 μg / L. The fact that ibuprofen is only soluble in water under alkaline conditions renders traditional biodegradation methods almost ineffective. Therefore, other methods that can effectively degrade ibuprofen under weakly alkaline conditions are needed. This invention, by controlling the preparation process, combines various metal oxides with C3N4 doping, achieving a 97.58% degradation rate of ibuprofen in the composite material under weakly alkaline conditions, effectively alleviating the pollution problem of ibuprofen in the natural environment.
[0025] (2) C3N4 combined with γ-Al2O3 and Cr2O3 forms Al2O3 / Cr2O3@C3N4 (ACC). The Al2O3 bridges Cr2O3 and C3N4, forming a double Z-type electron transfer path, which effectively inhibits the rapid recombination of charge carriers in C3N4. This allows conduction band electrons to accumulate on the surface of C3N4, generating highly oxidizing ·O2⁻ free radicals, which have a very good catalytic degradation effect on ibuprofen.
[0026] (3) The preparation process and raw materials of this invention have achieved the preparation of ternary Z-type semiconductor composite material. The two metal oxides combined with C3N4 greatly improve its photoresponsibility, so that it can generate photogenerated electrons under visible light. At the same time, the electron transfer path formed by the two oxides also improves the photogenerated carrier generation efficiency, so that the material can drive the reaction of degrading ibuprofen without high-energy ultraviolet light, which not only broadens the application scenarios of the material, but also greatly reduces the production cost.
[0027] (4) The preparation process and raw materials of this invention have achieved the preparation of ternary Z-type semiconductor composite material. The two metal oxides combined with C3N4 greatly improve its stability. The mass percentage of Al2O3 / Cr2O3 composite powder and porous graphitic carbon nitride powder is 5-50%. The ACC of Al2O3 / Cr2O3 composite powder and porous graphitic carbon nitride powder with a mass percentage of 20% still has a conversion rate of more than 90% after four cycles. Even after the fifth cycle, it still has an efficiency of 80.44%. It has good stability and can be used multiple times, and has good industrial potential.
[0028] (5) When ibuprofen is degraded using the ternary Z-type semiconductor composite material prepared by the present invention, the degradation products are short-chain carboxylic acids (such as 5-hydroxyvalerate and oxalic acid) that can participate in the natural carbon cycle. This composite material effectively solves the problem of ibuprofen being difficult to degrade in an alkaline environment and provides an efficient and environmentally friendly solution for drug pollution control. Attached Figure Description
[0029] Figure 1A preparation process, an electron microscope image and an energy spectrum analysis element distribution diagram of the composite material prepared in the application, wherein figure a is a preparation mechanism diagram of the ternary Z-type semiconductor composite material (ACC) responsive to visible light; figure b is a g-C3N4 substrate, figure c is an alumina and chromium oxide sintered in equal quality, figure d is the ACC with a mass percentage of 20% of Al2O3 / Cr2O3 composite powder and porous graphite phase carbon powder and porous graphite phase carbon powder, figure e is γ-Al2O3, figure f is chromium oxide, figure g is a 5µm scale SEM image of Cr2O3@C3N4 with a mass percentage of 20% of chromium oxide and graphite phase carbon, figure h is an energy spectrum analysis element distribution diagram of the ACC with a mass percentage of 20% of Al2O3 / Cr2O3 composite powder and porous graphite phase carbon powder; figure i is a 10µm scale SEM image of the ACC with a mass percentage of 20% of Al2O3 / Cr2O3 composite powder and porous graphite phase carbon powder, and figure j is a transmission electron microscope and high resolution TEM image of the ACC with a mass percentage of 20% of Al2O3 / Cr2O3 composite powder and porous graphite phase carbon powder.
[0030] Figure 2 A performance comparison diagram of the composite material prepared in the application for degrading ibuprofen. DETAILED DESCRIPTION
[0031] The application will be further described in conjunction with the drawings and specific examples, but the scope of protection of the application is not limited to the content described.
[0032] In the examples and comparative examples of the application, the chemical reagents not specifically mentioned are all commercially available analytical pure reagents for experiments.
[0033] Example 1 A preparation method of a ternary Z-type semiconductor composite material responsive to visible light, specifically comprising the following steps: (1) Potassium dichromate is prepared into an aqueous solution with a concentration of 80g / L, concentrated sulfuric acid is added to the aqueous solution of potassium dichromate at a mass-volume ratio of 2g:3mL of potassium dichromate and concentrated sulfuric acid, and the reaction is carried out for 30min, anhydrous ethanol is added to the solution after the reaction at a volume ratio of 10:3 of anhydrous ethanol and concentrated sulfuric acid, and then sodium hydroxide is added to adjust the pH value of the solution after the reaction to neutral.
[0034] (2) The solution after the pH adjustment is heated to 70℃, and then aluminum chloride and ammonia water with a mass percentage of 25% are added thereto at a mass-volume ratio of 1.35g:5mL:30mL of aluminum chloride, ammonia water and the solution after the pH adjustment, and the reaction is carried out for 2h, the solid product after the reaction is filtered, dried in an oven at 105℃ overnight, and then calcined in a muffle furnace at 430℃ for 4h, and the solid product after the calcination is ground to obtain Al2O3 / Cr2O3 composite powder.
[0035] (3) Put urea into a tube furnace, calcine at 550℃ for 2h under nitrogen atmosphere, obtain solid sample, stir the solid sample in 6mol / L hydrochloric acid solution for 4h, dry to obtain porous graphite phase carbon nitride powder.
[0036] (4) Weigh Al2O3 / Cr2O3 composite powder and porous graphite phase carbon nitride powder according to the mass percentage of 5%, mix them to form mixed powder, then treat the mixed powder with water suspension, then ultrasonic and stir for 4h, then centrifuge and dry in a vacuum drying oven at 60℃ overnight to obtain visible light responsive ternary Z-type semiconductor composite material Al2O3 / Cr2O3@C3N4 (ACC).
[0037] The morphology of the ternary Z-type semiconductor composite material prepared in this embodiment is observed, and it is found through testing that the graphite phase of the material presents a layered structure, showing a large specific surface area and rich surface adsorption reaction sites; the interatomic bonding force of Al2O3 / Cr2O3 is enhanced, and the composite efficiency is significantly improved; energy spectrum analysis shows that the semiconductor additive is uniformly combined with the catalyst.
[0038] Prepare a reaction solution with a concentration of 2mg / L of ibuprofen (IBU), adjust the pH value of the reaction solution to 7.9 with sodium hydroxide, keep the reaction volume at 100mL, and the temperature at 25℃. Add the ternary Z-type semiconductor composite material prepared in Example 1 with a mass percentage of 5% of Al2O3 / Cr2O3 composite powder and porous graphite phase carbon nitride powder to it to evaluate the effect of the composite material on the degradation and adsorption of ibuprofen. The specific test conditions are as follows: use a 300W xenon lamp and a 400nm filter to eliminate ultraviolet light, and use a mass spectrometer to measure the concentration of ibuprofen and reaction intermediates to evaluate the reaction activity. It is found that the ternary Z-type semiconductor composite material prepared in Example 1 has an adsorption rate of 4.79% for ibuprofen and a degradation rate of 96.27%, and does not cause secondary pollution to the environment, which indicates that the heterostructure material can enhance the carrier separation and transfer efficiency; in addition, the ternary Z-type semiconductor composite material prepared in this embodiment can be used repeatedly. Figure 2
[0039] Example 2 A method for preparing a visible light responsive ternary Z-type semiconductor composite material, specifically comprising the following steps: (1) Prepare a potassium dichromate solution of 80g / L, add concentrated sulfuric acid to the potassium dichromate solution according to the mass volume ratio of 2g:3mL, and react for 30min, then add anhydrous ethanol to the solution after reaction according to the volume ratio of 10:3, then add sodium hydroxide to adjust the pH value of the solution after reaction to neutral.
[0040] (2) Heat the pH-adjusted solution to 70°C, then add aluminum chloride and ammonia water in a ratio of 1.35 g: 5 mL: 30 mL to 25% by mass of the pH-adjusted solution and react for 2 h. Filter the solid product after the reaction and dry it overnight in an oven at 105°C. Then calcine it in a muffle furnace at 430°C for 4 h. Grind the calcined solid product to obtain Al2O3 / Cr2O3 composite powder.
[0041] (3) Place urea in a tube furnace and calcine it at 550°C for 2 hours under a nitrogen atmosphere to obtain a solid sample. The solid sample is then washed with 6 mol / L hydrochloric acid aqueous solution for 4 hours and dried to obtain porous graphitic carbon nitride powder.
[0042] (4) Weigh out Al2O3 / Cr2O3 composite powder and porous graphitic carbon nitride powder in a ratio of 10% by mass and mix them to form a mixed powder. Then, suspend the mixed powder in water, sonicate and stir for 4 hours, then centrifuge and dry overnight in a vacuum drying oven at 60°C to obtain visible light responsive ternary Z-type semiconductor composite material Al2O3 / Cr2O3@C3N4(ACC).
[0043] Morphological observation of the ternary Z-type semiconductor composite material prepared in this embodiment revealed that the graphite phase of the material exhibits a layered structure, showing a large specific surface area and abundant surface adsorption reaction sites; the interatomic bonding force of Al2O3 / Cr2O3 is enhanced, and the composite efficiency is significantly improved; energy dispersive spectroscopy analysis shows that the semiconductor additive and catalyst are uniformly combined.
[0044] The Al2O3 / Cr2O3 composite powder prepared in Example 2 and a ternary Z-type semiconductor composite material containing 10% (by mass) of porous graphitic carbon nitride powder were used to degrade and adsorb ibuprofen. The specific operation was the same as in Example 1. Figure 2 The ternary Z-type semiconductor composite material prepared in Example 2 showed an adsorption rate of 1.64% and a degradation rate of 96.67% for ibuprofen, without causing secondary pollution to the environment. This indicates that heterogeneous structure materials can enhance carrier separation and transfer efficiency. In addition, the ternary Z-type semiconductor composite material prepared in this example can be recycled multiple times.
[0045] Example 3 A method for preparing a visible light-responsive ternary Z-type semiconductor composite material specifically includes the following steps: (1) Prepare an 80 g / L aqueous solution of potassium dichromate. Add concentrated sulfuric acid to the potassium dichromate aqueous solution at a mass-volume ratio of 2 g:3 mL and react for 30 min. Add anhydrous ethanol to the solution after reaction at a volume ratio of 10:3. Then add sodium hydroxide and adjust the pH of the solution after reaction to neutral.
[0046] (2) Heat the pH-adjusted solution to 70°C, then add aluminum chloride and ammonia water in a ratio of 1.35 g: 5 mL: 30 mL to 25% by mass of the pH-adjusted solution and react for 2 h. Filter the solid product after the reaction and dry it overnight in an oven at 105°C. Then calcine it in a muffle furnace at 430°C for 4 h. Grind the calcined solid product to obtain Al2O3 / Cr2O3 composite powder.
[0047] (3) Place urea in a tube furnace and calcine it at 550°C for 2 hours under a nitrogen atmosphere to obtain a solid sample. The solid sample is then washed with 6 mol / L hydrochloric acid aqueous solution for 4 hours and dried to obtain porous graphitic carbon nitride powder.
[0048] (4) Weigh out Al2O3 / Cr2O3 composite powder and porous graphitic carbon nitride powder at a mass percentage of 20% and mix them to form a mixed powder. Then, suspend the mixed powder in water, sonicate and stir for 4 hours, then centrifuge and dry overnight at 60°C in a vacuum drying oven to obtain visible light responsive ternary Z-type semiconductor composite material Al2O3 / Cr2O3@C3N4(ACC).
[0049] The morphology of the ternary Z-type semiconductor composite material prepared in this embodiment was observed, such as... Figure 1 As shown, the graphitic C3N4 phase exhibits a layered structure, demonstrating a large specific surface area and abundant surface adsorption reaction sites; the Al2O3 / Cr2O3 prepared by the one-pot method shows enhanced interatomic bonding forces and significantly improved recombination efficiency. With increased scale, semiconductor materials are nested within the multilayered structure of C3N4 (…). Figure 1 d, i). Amorphous alumina covering a hexagonal chromium oxide structure constructs a hexagonal crystal system; energy dispersive spectroscopy analysis shows that aluminum, chromium, and oxygen are uniformly distributed (d, i). Figure 1 h), these elements are relatively evenly distributed on the catalyst surface, proving that the semiconductor additives are uniformly combined with the catalyst.
[0050] The Al2O3 / Cr2O3 composite powder prepared in Example 3 and a ternary Z-type semiconductor composite material containing 20% (by mass) of porous graphitic carbon nitride powder were used to degrade and adsorb ibuprofen. The specific operation was the same as in Example 1.Figure 2 The ternary Z-type semiconductor composite material prepared in Example 3 showed an adsorption rate of 1.79% and a degradation rate of 97.58% for ibuprofen, without causing secondary pollution to the environment. This indicates that heterogeneous structure materials can enhance carrier separation and transfer efficiency. In addition, the ternary Z-type semiconductor composite material prepared in this example can be recycled multiple times.
[0051] The composite material prepared in this embodiment has high photocurrent intensity and carrier separation efficiency, which meets the requirements of photocatalytic decomposition reaction. With the addition of metal oxides, the material can react under visible light, reducing the high cost of ultraviolet light. At the same time, the material was subjected to cyclic testing and still maintained a reaction efficiency of >80% after five cycles, which can be reused multiple times, greatly reducing the cost of use.
[0052] Example 4 A method for preparing a visible light-responsive ternary Z-type semiconductor composite material specifically includes the following steps: (1) Prepare an 80 g / L aqueous solution of potassium dichromate. Add concentrated sulfuric acid to the potassium dichromate aqueous solution at a mass-volume ratio of 2 g:3 mL and react for 30 min. Add anhydrous ethanol to the solution after reaction at a volume ratio of 10:3. Then add sodium hydroxide and adjust the pH of the solution after reaction to neutral.
[0053] (2) Heat the pH-adjusted solution to 70°C, then add aluminum chloride and ammonia water in a ratio of 1.35 g: 5 mL: 30 mL to 25% by mass of the pH-adjusted solution and react for 2 h. Filter the solid product after the reaction and dry it overnight in an oven at 105°C. Then calcine it in a muffle furnace at 430°C for 4 h. Grind the calcined solid product to obtain Al2O3 / Cr2O3 composite powder.
[0054] (3) Place urea in a tube furnace and calcine it at 550°C for 2 hours under a nitrogen atmosphere to obtain a solid sample. The solid sample is then washed with 6 mol / L hydrochloric acid aqueous solution for 4 hours and dried to obtain porous graphitic carbon nitride powder.
[0055] (4) Weigh Al2O3 / Cr2O3 composite powder and porous graphitic carbon nitride powder at a mass percentage of 30% and mix them to form a mixed powder. Then, suspend the mixed powder in water, sonicate and stir for 4 hours, then centrifuge and dry overnight at 60°C in a vacuum drying oven to obtain visible light responsive ternary Z-type semiconductor composite material Al2O3 / Cr2O3@C3N4(ACC).
[0056] Morphological observation of the ternary Z-type semiconductor composite material prepared in this embodiment revealed that the graphite phase of the material exhibits a layered structure, showing a large specific surface area and abundant surface adsorption reaction sites; the interatomic bonding force of Al2O3 / Cr2O3 is enhanced, and the composite efficiency is significantly improved; energy dispersive spectroscopy analysis shows that the semiconductor additive and catalyst are uniformly combined.
[0057] The Al2O3 / Cr2O3 composite powder prepared in Example 4 and a ternary Z-type semiconductor composite material containing 30% (by mass) of porous graphitic carbon nitride powder were used to degrade and adsorb ibuprofen. The specific operation was the same as in Example 1. Figure 2 The ternary Z-type semiconductor composite material prepared in Example 4 showed an adsorption rate of 0.89% and a degradation rate of 96.45% for ibuprofen, without causing secondary pollution to the environment. This indicates that heterogeneous materials can enhance carrier separation and transfer efficiency. In addition, the ternary Z-type semiconductor composite material prepared in this example can be recycled multiple times.
[0058] Example 5 A method for preparing a visible light-responsive ternary Z-type semiconductor composite material specifically includes the following steps: (1) Prepare an 80 g / L aqueous solution of potassium dichromate. Add concentrated sulfuric acid to the potassium dichromate aqueous solution at a mass-volume ratio of 2 g:3 mL and react for 30 min. Add anhydrous ethanol to the solution after reaction at a volume ratio of 10:3. Then add sodium hydroxide and adjust the pH of the solution after reaction to neutral.
[0059] (2) Heat the pH-adjusted solution to 70°C, then add aluminum chloride and ammonia water in a ratio of 1.35 g: 5 mL: 30 mL to 25% by mass of the pH-adjusted solution and react for 2 h. Filter the solid product after the reaction and dry it overnight in an oven at 105°C. Then calcine it in a muffle furnace at 430°C for 4 h. Grind the calcined solid product to obtain Al2O3 / Cr2O3 composite powder.
[0060] (3) Place urea in a tube furnace and calcine it at 550°C for 2 hours under a nitrogen atmosphere to obtain a solid sample. The solid sample is then washed with 6 mol / L hydrochloric acid aqueous solution for 4 hours and dried to obtain porous graphitic carbon nitride powder.
[0061] (4) Weigh Al2O3 / Cr2O3 composite powder and porous graphitic carbon nitride powder at a mass percentage of 40% and mix them to form a mixed powder. Then, suspend the mixed powder in water, sonicate and stir for 4 hours, then centrifuge and dry overnight at 60°C in a vacuum drying oven to obtain visible light responsive ternary Z-type semiconductor composite material Al2O3 / Cr2O3@C3N4(ACC).
[0062] Morphological observation of the ternary Z-type semiconductor composite material prepared in this embodiment revealed that the graphite phase of the material exhibits a layered structure, showing a large specific surface area and abundant surface adsorption reaction sites; the interatomic bonding force of Al2O3 / Cr2O3 is enhanced, and the composite efficiency is significantly improved; energy dispersive spectroscopy analysis shows that the semiconductor additive and catalyst are uniformly combined.
[0063] The Al2O3 / Cr2O3 composite powder prepared in Example 5 and a ternary Z-type semiconductor composite material containing 40% (by mass) of porous graphitic carbon nitride powder were used to degrade and adsorb ibuprofen. The specific operation was the same as in Example 1. Figure 2 The ternary Z-type semiconductor composite material prepared in Example 5 showed an adsorption rate of 1.46% for ibuprofen and a degradation rate of 95.87%, without causing secondary pollution to the environment. This indicates that heterogeneous structure materials can enhance carrier separation and transfer efficiency. In addition, the ternary Z-type semiconductor composite material prepared in this example can be recycled multiple times.
[0064] Example 6 A method for preparing a visible light-responsive ternary Z-type semiconductor composite material specifically includes the following steps: (1) Prepare an 80 g / L aqueous solution of potassium dichromate. Add concentrated sulfuric acid to the potassium dichromate aqueous solution at a mass-volume ratio of 2 g:3 mL and react for 30 min. Add anhydrous ethanol to the solution after reaction at a volume ratio of 10:3. Then add sodium hydroxide and adjust the pH of the solution after reaction to neutral.
[0065] (2) Heat the pH-adjusted solution to 70°C, then add aluminum chloride and ammonia water in a ratio of 1.35 g: 5 mL: 30 mL to 25% by mass of the pH-adjusted solution and react for 2 h. Filter the solid product after the reaction and dry it overnight in an oven at 105°C. Then calcine it in a muffle furnace at 430°C for 4 h. Grind the calcined solid product to obtain Al2O3 / Cr2O3 composite powder.
[0066] (3) Place urea in a tube furnace and calcine it at 550°C for 2 hours under a nitrogen atmosphere to obtain a solid sample. The solid sample is then washed with 6 mol / L hydrochloric acid aqueous solution for 4 hours and dried to obtain porous graphitic carbon nitride powder.
[0067] (4) Weigh out Al2O3 / Cr2O3 composite powder and porous graphitic carbon nitride powder in a mass percentage ratio of 50% and mix them to form a mixed powder. Then, suspend the mixed powder in water, sonicate and stir for 4 hours, then centrifuge and dry overnight in a vacuum drying oven at 60°C to obtain visible light responsive ternary Z-type semiconductor composite material Al2O3 / Cr2O3@C3N4(ACC).
[0068] Morphological observation of the ternary Z-type semiconductor composite material prepared in this embodiment revealed that the graphite phase of the material exhibits a layered structure, showing a large specific surface area and abundant surface adsorption reaction sites; the interatomic bonding force of Al2O3 / Cr2O3 is enhanced, and the composite efficiency is significantly improved; energy dispersive spectroscopy analysis shows that the semiconductor additive and catalyst are uniformly combined.
[0069] The Al2O3 / Cr2O3 composite powder prepared in Example 6 and a ternary Z-type semiconductor composite material with a mass percentage of 50% porous graphitic carbon nitride powder were used to degrade and adsorb ibuprofen. The specific operation was the same as in Example 1. Figure 2 The ternary Z-type semiconductor composite material prepared in Example 6 showed an adsorption rate of 1.11% for ibuprofen and a degradation rate of 95.69%, without causing secondary pollution to the environment. This indicates that heterogeneous structure materials can enhance carrier separation and transfer efficiency. In addition, the ternary Z-type semiconductor composite material prepared in this example can be recycled multiple times.
[0070] Example 7 A method for preparing a visible light-responsive ternary Z-type semiconductor composite material specifically includes the following steps: (1) Prepare an 80 g / L aqueous solution of potassium dichromate. Add concentrated sulfuric acid to the potassium dichromate aqueous solution at a mass-volume ratio of 2 g:3 mL and react for 30 min. Add anhydrous ethanol to the solution after reaction at a volume ratio of 10:3. Then add sodium hydroxide and adjust the pH of the solution after reaction to neutral.
[0071] (2) Heat the pH-adjusted solution to 70°C, then add aluminum chloride and ammonia water in a ratio of 1.35 g: 5 mL: 30 mL to 25% by mass of the pH-adjusted solution and react for 3 h. Filter the solid product after the reaction and dry it overnight in an oven at 105°C. Then calcine it in a muffle furnace at 380°C for 5 h. Grind the calcined solid product to obtain Al2O3 / Cr2O3 composite powder.
[0072] (3) Place urea in a tube furnace and calcine it at 520°C for 3 hours under a nitrogen atmosphere to obtain a solid sample. The solid sample is then washed with 6 mol / L hydrochloric acid aqueous solution for 4 hours and dried to obtain porous graphitic carbon nitride powder.
[0073] (4) Weigh out Al2O3 / Cr2O3 composite powder and porous graphitic carbon nitride powder at a mass percentage of 20% and mix them to form a mixed powder. Then, suspend the mixed powder in water, sonicate and stir for 4 hours, then centrifuge and dry overnight at 60°C in a vacuum drying oven to obtain visible light responsive ternary Z-type semiconductor composite material Al2O3 / Cr2O3@C3N4(ACC).
[0074] Morphological observation of the ternary Z-type semiconductor composite material prepared in this embodiment revealed that the graphite phase of the material exhibits a layered structure, showing a large specific surface area and abundant surface adsorption reaction sites; the interatomic bonding force of Al2O3 / Cr2O3 is enhanced, and the composite efficiency is significantly improved; energy dispersive spectroscopy analysis shows that the semiconductor additive and catalyst are uniformly combined.
[0075] The ternary Z-type semiconductor composite material, consisting of Al2O3 / Cr2O3 composite powder and porous graphitic carbon nitride powder at a mass percentage of 20%, prepared in Example 7, was used to degrade and adsorb ibuprofen. The specific operation was the same as in Example 1. Tests showed that the ternary Z-type semiconductor composite material prepared in Example 7 had excellent adsorption and degradation rates for ibuprofen (IBU degradation rate of over 95% after 6 hours) and did not cause secondary pollution to the environment. This indicates that heterogeneous structure materials can enhance carrier separation and transfer efficiency. In addition, the ternary Z-type semiconductor composite material prepared in this example can be recycled multiple times.
[0076] Example 8 A method for preparing a visible light-responsive ternary Z-type semiconductor composite material specifically includes the following steps: (1) Prepare an 80 g / L aqueous solution of potassium dichromate. Add concentrated sulfuric acid to the potassium dichromate aqueous solution at a mass-volume ratio of 2 g:3 mL and react for 30 min. Add anhydrous ethanol to the solution after reaction at a volume ratio of 10:3. Then add sodium hydroxide and adjust the pH of the solution after reaction to neutral.
[0077] (2) Heat the pH-adjusted solution to 70°C, then add aluminum chloride and ammonia water in a mass-volume ratio of 1.35g:5mL:30mL to the solution after pH adjustment and react for 2.5h. Filter the solid product after the reaction and dry it overnight in an oven at 105°C. Then calcine it in a muffle furnace at 400°C for 4.5h. Grind the calcined solid product to obtain Al2O3 / Cr2O3 composite powder.
[0078] (3) Place urea in a tube furnace and calcine it at 580°C for 2.5 h under a nitrogen atmosphere to obtain a solid sample. The solid sample is then washed with 6 mol / L hydrochloric acid aqueous solution for 4 h and dried to obtain porous graphitic carbon nitride powder.
[0079] (4) Weigh out Al2O3 / Cr2O3 composite powder and porous graphitic carbon nitride powder at a mass percentage of 20% and mix them to form a mixed powder. Then, suspend the mixed powder in water, sonicate and stir for 4 hours, then centrifuge and dry overnight at 60°C in a vacuum drying oven to obtain visible light responsive ternary Z-type semiconductor composite material Al2O3 / Cr2O3@C3N4(ACC).
[0080] Morphological observation of the ternary Z-type semiconductor composite material prepared in this embodiment revealed that the graphite phase of the material exhibits a layered structure, showing a large specific surface area and abundant surface adsorption reaction sites; the interatomic bonding force of Al2O3 / Cr2O3 is enhanced, and the composite efficiency is significantly improved; energy dispersive spectroscopy analysis shows that the semiconductor additive and catalyst are uniformly combined.
[0081] The ternary Z-type semiconductor composite material, consisting of Al2O3 / Cr2O3 composite powder and porous graphitic carbon nitride powder at a mass percentage of 20%, prepared in Example 8, was used to degrade and adsorb ibuprofen. The specific operation was the same as in Example 1. Tests showed that the ternary Z-type semiconductor composite material prepared in Example 8 had excellent adsorption and degradation rates for ibuprofen (IBU degradation rate was over 95% after 6 hours) and did not cause secondary pollution to the environment. This indicates that heterogeneous structure materials can enhance carrier separation and transfer efficiency. In addition, the ternary Z-type semiconductor composite material prepared in this example can be recycled multiple times.
[0082] Comparative Example 1 The preparation method of porous graphitic carbon nitride specifically includes the following steps: Urea was placed in a tube furnace and calcined at 550°C for 2 hours under a nitrogen atmosphere to obtain a solid sample. The solid sample was then acid-washed with a 6 mol / L hydrochloric acid aqueous solution for 4 hours and dried at 105°C for 4 hours to obtain porous graphitic carbon nitride powder.
[0083] The porous graphitic carbon nitride prepared in Comparative Example 1 was used to adsorb and degrade ibuprofen, and the specific operation was the same as in Example 1. Figure 2 The composite material prepared in Comparative Example 1 showed an adsorption rate of 10.26% for ibuprofen in the dark within 30 min and a degradation rate of 29.59% in 6 h, without causing secondary pollution to the environment.
[0084] Comparative Example 2 This comparative example is a blank control group, meaning no materials were prepared for the degradation of ibuprofen.
[0085] The ibuprofen degradation rate of the blank control group was tested, and the specific operation was the same as in Example 1. The test results showed that the degradation rate of ibuprofen in Comparative Example 2 was only 5.14%, and no secondary pollution was caused to the environment. Figure 2 Without the addition of a catalyst (Comparative Example 2), the degradation rate of IBU within 6 hours was close to 5.14%, indicating that its self-photolysis ability is limited.
[0086] Comparative Example 3 The preparation method of Al2O3@C3N4 specifically includes the following steps: (1) Add aluminum chloride and ammonia water at a mass percentage of 25% and a solution mass-volume ratio of 1.35g:5mL:30mL and react for 2 hours. Filter the solid product after the reaction and dry it overnight at 105℃ in an oven. Then calcine it at 430℃ in a muffle furnace for 4 hours. Grind the calcined solid product to obtain Al2O3 powder.
[0087] (3) Place urea in a tube furnace and calcine it at 580°C for 2.5 h under a nitrogen atmosphere to obtain a solid sample. The solid sample is then washed with 6 mol / L hydrochloric acid aqueous solution for 4 h and dried to obtain porous graphitic carbon nitride powder.
[0088] (4) Weigh Al2O3 powder and porous graphitic carbon nitride powder at a mass percentage of 20% and mix them to form a mixed powder. Then, suspend the mixed powder in water, sonicate and stir for 4 hours, then centrifuge and dry overnight in a vacuum drying oven at 60°C to obtain visible light responsive binary Z-type semiconductor composite material Al2O3@C3N4.
[0089] Depend on Figure 1 It can be seen that when Al2O3 is sintered under the same conditions as that for Al2O3 / Cr2O3 composites, the material exhibits a clustered amorphous structure (e.g., Figure 1 As shown in e, SEM observation reveals that the surface is plated with gold particles.
[0090] The Al2O3 powder prepared in Comparative Example 3 and the Al2O3@C3N4 material with a mass percentage of 20% porous graphitic carbon nitride powder were used to degrade and adsorb ibuprofen. The specific operation was the same as in Example 1. Figure 2 The results showed that the binary Z-type semiconductor composite material prepared in Comparative Example 3 had an adsorption rate of 5.44% and a degradation rate of 34.06% for ibuprofen, and did not cause secondary pollution to the environment, indicating that the catalytic effect of C3N4 combined with a single metal oxide still needs to be improved.
[0091] Comparative Example 4 The preparation method of Cr2O3@C3N4 specifically includes the following steps: (1) Potassium dichromate was prepared into an 80 g / L aqueous solution. Concentrated sulfuric acid was added to the potassium dichromate aqueous solution at a mass-volume ratio of 2 g:3 mL and reacted for 30 min. Anhydrous ethanol was added to the solution after the reaction at a volume ratio of 10:3. Then sodium hydroxide was added to adjust the pH of the solution after the reaction to neutral. The solid product after the reaction was completed was filtered, dried overnight at 105 °C in an oven, and then calcined at 430 °C for 4 h in a muffle furnace. The calcined solid product was ground to obtain Cr2O3 powder.
[0092] (3) Place urea in a tube furnace and calcine it at 550°C for 2 hours under a nitrogen atmosphere to obtain a solid sample. The solid sample is then washed with 6 mol / L hydrochloric acid aqueous solution for 4 hours and dried to obtain porous graphitic carbon nitride powder.
[0093] (4) Weigh Cr2O3 powder and porous graphitic carbon nitride powder at a mass percentage of 20% and mix them to form a mixed powder. Then, suspend the mixed powder in water, sonicate and stir for 4 hours, then centrifuge and dry overnight in a vacuum drying oven at 60°C to obtain the visible light responsive binary Z-type semiconductor composite material Cr2O3@C3N4.
[0094] Depend on Figure 1 It can be seen that when Cr2O3 is sintered under the same conditions as that for sintering Al2O3 / Cr2O3 composites (such as...), Figure 1 As shown in f, during sintering under the same conditions, the material forms loose pores on the surface due to dehydration, causing the hydroxyl groups on the surface to fall off, thus affecting the loading efficiency and stability of the heterojunction (e.g., as shown in f).Figure 1 (as shown in g).
[0095] The Cr2O3 powder and porous graphitic carbon nitride powder prepared in Comparative Example 4, with a mass percentage of 20%, Cr2O3@C3N4 material was used to degrade and adsorb ibuprofen. The specific operation was the same as in Example 1. Figure 2 The results showed that the binary Z-type semiconductor composite material prepared in Comparative Example 4 had an adsorption rate of 2.44% and a degradation rate of 45.40% for ibuprofen, and did not cause secondary pollution to the environment, indicating that the catalytic effect of C3N4 combined with a single metal oxide still needs to be improved.
[0096] The materials prepared in Examples 1-6 and Comparative Examples 1-4 were tested for their adsorption and ibuprofen degradation performance. The specific test results are shown in Table 1.
[0097] Table 1 As shown in Table 1, C3N4 exhibits good photoresponsiveness, but its rapid carrier recombination rate limits its catalytic performance. By introducing metal oxides with different loading amounts, the carrier recombination problem is effectively solved, and the photocurrent is greatly enhanced, resulting in excellent ibuprofen degradation rate. This reduces costs while improving catalytic efficiency, and the process does not cause any environmental pollution. It provides a novel method and approach for treating ibuprofen under natural conditions.
[0098] The comparison between the examples and comparative examples shows that the addition of C3N4 or metal oxides significantly improves the photocatalytic performance of the materials. Other preparation methods not used in this invention, or whose raw material components are not within the scope of this invention, result in composite materials with poor performance.
[0099] The various embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. The terminology used herein is chosen to best explain the principles, practical application, or improvement of the technology in the market, or to enable others skilled in the art to understand the embodiments disclosed herein.
Claims
1. A visible light-responsive ternary Z-type semiconductor composite material, characterized in that, The ternary Z-type semiconductor composite material is a heterojunction formed by nesting Al2O3 / Cr2O3 composite and protonated C3N4 in a mass percentage ratio of 5-50%.
2. The visible light-responsive ternary Z-type semiconductor composite material according to claim 1, characterized in that, The Al2O3 is in γ-crystalline form; the Cr2O3 is in hexahedral crystalline form; and the protonated C3N4 is a layered porous graphitic carbon nitride loaded with amorphous alumina and coated with hexagonal chromium oxide.
3. The method for preparing the visible light-responsive ternary Z-type semiconductor composite material according to claim 1, characterized in that, Specifically, the following steps are included: (1) Prepare an aqueous solution of potassium dichromate, add concentrated sulfuric acid to the potassium dichromate aqueous solution to react, add organic solvent and alkali to the solution after reaction, and adjust the pH value of the solution. (2) Heat the solution after adjusting the pH, then add aluminum chloride and ammonia to react, filter and dry the solid product after the reaction, then calcine it, and grind the calcine solid product to obtain Al2O3 / Cr2O3 composite powder. (3) Calcine urea to obtain a solid sample, and then wash and dry the solid sample to obtain porous graphitic carbon nitride powder; (4) Weigh Al2O3 / Cr2O3 composite powder and porous graphitic carbon nitride powder in proportion and mix them to form a mixed powder. Then, suspend the mixed powder in water, sonicate and stir, and then centrifuge and dry to obtain a visible light responsive ternary Z-type semiconductor composite material.
4. The method for preparing the visible light-responsive ternary Z-type semiconductor composite material according to claim 3, characterized in that, In step (1), the concentration of the potassium dichromate aqueous solution is 80 g / L; the concentrated sulfuric acid is added to the potassium dichromate aqueous solution at a mass-volume ratio of 2 g: 3 mL; the reaction time of the concentrated sulfuric acid added to the potassium dichromate aqueous solution is 30 min.
5. The method for preparing the visible light-responsive ternary Z-type semiconductor composite material according to claim 3, characterized in that, In step (1), the organic solvent is anhydrous ethanol, and the organic solvent is added to the solution after the reaction at a volume ratio of 10:3 to concentrated sulfuric acid; the base is sodium hydroxide; and the pH of the solution after the reaction is adjusted to neutral.
6. The method for preparing the visible light-responsive ternary Z-type semiconductor composite material according to claim 3, characterized in that, In step (2), the solution after pH adjustment is heated to 70°C; aluminum chloride and ammonia are added to the solution after pH adjustment in a mass-volume ratio of 1.35g:5mL:30mL; the mass percentage concentration of ammonia is 25%; the reaction time of aluminum chloride, ammonia and pH-adjusted solution is 2-3 hours.
7. The method for preparing the visible light-responsive ternary Z-type semiconductor composite material according to claim 3, characterized in that, In step (2), the solid product is dried at 105°C overnight; the solid product is roasted at 380-430°C for 4-5 hours.
8. The method for preparing the visible light-responsive ternary Z-type semiconductor composite material according to claim 3, characterized in that, The calcination conditions in step (3) are: calcination at 520-580℃ for 2-3 hours under a nitrogen atmosphere; the acid washing process is to stir and acid wash the solid sample with a 6mol / L hydrochloric acid aqueous solution for 4 hours.
9. The method for preparing the visible light-responsive ternary Z-type semiconductor composite material according to claim 3, characterized in that, The mixing time of the mixed powder in the suspension treatment in step (4) is 4 hours; the drying conditions of the mixed powder are: drying at 60°C overnight.
10. The application of the visible light-responsive ternary Z-type semiconductor composite material of claim 1 in the catalytic degradation of ibuprofen in water.
